Pusat Perbelanjaaan Modern Di Teluk Kuantan Dengan Pendekatan Arsitektur Modern - Rakhmat Minanggi Purba; Wahyu Hidayat; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Teluk Kuantan is the capital of Kuantan Singingi district. Teluk Kuantan as expansion city needs to build public facilities one of which is modern shopping center. It is important because todescribe progress of a city and also can improve community economy matters. Modern shopping center in Teluk Kuantan apply of theme modern architecture by using an organic concept. Organic according to Iain Thomson in book of A Visual Encyclopedia of Frank Lloyd Wright is planning and designing by taking the resources from nature in the form of living creatures or related to living organism, as main of the form and function of the building. Design of shopping centers by using nature as a basic concept of the building can be applied if the chosen site has natural potential. In designing a modern shopping center there are some factors that need to be considered. These factors among the selection of appropriate area, designing buildings that can provide comfort for visitors, the use of the structure proper construction, material selection, and implementation of the utility system. Then it is necessary to formulate the ways of planning and designing of shopping centers in accordance with applicable standards.Keywords: Modern Shopping Center, Organic, Principles of Modern Architectural Design